PENGARUH KEMAMPUAN TEKNIK PERSONAL DAN PELATIHAN KERJA PADA KINERJA SISTEM INFORMASI AKUNTANSI - Mariana Putra, I Made Rai; Juliarsa, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The performance of the accounting information system is the result or level of success of the accounting information system in carrying out tasks during a specific period which is indicated by satisfaction by the user of the system and users of accounting information systems.  An accounting information system that produces good performance will make it easier to provide accountability to stakeholders in the form of financial statements in accordance with standards applicable to financial accounting.  However, there are often obstacles, namely human error in the operation of an accounting information system which is caused by inaccurate, relevant, and precise system performance results.   time. The purpose of this study is to determine the ability of personal techniques and job training that affects the performance of accounting information systems. This research was conducted at PT BPR Bank Daerah Bangli (Perseroda), the number of samples used was 33 employees with the purposive sampling method. Data collection was carried out using a survey approach, where the research instrument used was a questionnaire. The collected data was then analyzed using multiple linear regression analysis techniques. The results showed that personal engineering skills have a positive and significant effect on the performance of accounting information systems.  Job training has a significant positive effect on the performance of the accounting information system at PT BPR Bank Daerah Bangli (Perseroda).